Ideał mędrca w listach św. Ambrożego - Wysocki, Marcin (Vox Patrum, 2015)
St. Ambrose’s letters are a unique example of bishop’s concern for pastoral, social and political issues relating to the city, the diocese, the Empire and the Church. They have been a special way of his pastoral influence and work. He included in them a number of moral, legal and dogmatic instructions, among which he described a model of the Christian sage. It was based on the statements of the Stoic philosophy, but finally the Christian character arising from Scripture, and especially from the teaching of St. Paul the Apostle, was added to Ambrose’s model of a sage. According to Ambrose, the basic feature of the sage is freedom, but it also provides a number of other features – such as submission to God, love for the neighbours, the spirit of repentance, knowledge of God’s Law – which constitute the perfect sage, and ultimately – the perfect Christian.